Future intelligent vehicular technologies : first International Conference, Future 5V 2016, Porto, Portugal, September 15, 2016, Revised selected papers /: first International Conference, Future 5V 2016, Porto, Portugal, September 15, 2016, Revised selected papers. (2017) - Unknown
No abstract available